Flow variability along a vegetated natural stream under various sediment transport rates - Wang, Hai-zhou; Xu, Ze-xing; Yu, Hai-ti; Wang, Xie-kang (Journal of mountain science, 2018)
The influence of vegetation and sediment on flow characteristics in open channels cannot be neglected. To study the flow variability under the effects of the instream natural vegetation and sediment supply, experiments were conducted with varied water and sediment supply in a movable bed of a river prototype. The instantaneous three-dimensional velocities near two types of vegetation patches (the shrub and the weed) and along the centerline of the main channel with vegetation belts were measured using a 3-D side-looking acoustic Doppler velocimetry. The experimental results show that both the instream vegetation and sediment supply strongly affect the flow and turbulence characteristics. In the case of vegetation patches, both the shrub and weed have a considerable influence on the distribution of the streamwise velocity and turbulence intensity of their surrounding water. The streamwise velocity distribution followed as J-shape and linear shape around the weed and shrub under different experimental conditions. The turbulence intensity was large at the top of the weed and shrub; the shrub had its greatest influence on the downstream water flow. In the case of vegetation belts, the streamwise velocity along the centerline of the main channel exhibited an S-shape, J-shape and linear shape at different locations under varied water, vegetation structures and riverbed configurations. The turbulence intensity along the centerline of the main channel ranged from 0.0 to 0.1. The upstream turbulence intensity was affected considerably by a sediment supply, while the downstream turbulence intensity changed with the varied vegetation characteristics and riverbed topography. The second flow coefficient M -value increased longitudinally and was almost positive along the centerline of the main channel, implying that the rotational direction of the secondary current cell was clockwise.